Effect of planting time and density on plant growth, seed yield and quality attributes in onion (Allium cepa) cv. Pusa Riddhi - KUMAR, SANJAY; TOMAR, B S; JAIN, S K; SINGH, NAVEEN; PARSAD, RAJENDER; MUNSHI, A D (The Indian Journal of Agricultural Sciences, 2015)
The present experiment was conducted to investigate the effect of planting time and density on plant growth, seed yield and quality attributes in onion (Allium cepa L.) cv. Pusa Riddhi at SPU, IARI, New Delhi during rabi 2013-14 and 2014-15. The experiment consists of three different planting dates, i.e. 15 October (T1), 25 October (T2) and 5 November (T3) with three spacings, viz. 60×10 cm (S1) 60×20 cm (S2) 60×30 cm (S3). The experimental results revealed that the date of planting and plant spacing had significant influence on growth attributes, flowering, yield and quality characters. The planting on 15 October (T1) showed significant higher, seed scape height (101.4 cm), umbel diameter (6.54 cm), productive umbellates/umbel (414.73), seed setting (83.69%), seed yield/plant (8.71 g) and yield/ ha (6.86 q), germination (%) (88.43), seedling length (9.48 cm), seedling dry weight (1.9 mg) and vigour index-I and II (8.33.32 and 167.08) than 25 October and 5 November planting. The plant spacing 60×30cm (S3) showed higher number of leaves/plant (40.89) seed scape height (102.26 cm), scape diameter (1.88 cm), total scapes/plant (11.72), umbel diameter (6.58 cm), productive scapes/plant (8.35), umbellates/umbel (503.52), productive umbellates/umbel (419.4), yield/umbel (3.48 g), seed yield/plant (12.43 g), seed yield/ha (6.22 q), 1000 seed weight (3.01 g), germination (%) (89.76) and seed vigour-I and II (918.56 and 172.96) than closer spacing. The incidence of disease, disease severity index and scape lodging (%) were significantly lower in 15 October (T1) and 60×30 (S3).